THE INTERIM EXPERTS’ COUNCIL RESOLUTION ON THE EMPA-REG OUTCOME TRIAL ISSUES - M. V. Shestakova; S. A. Boytsov; O. M. Drapkina; T. Yu. Demidova; H. Drexel; M. B. Antsiferov; N. A. Petunina; N. A. Chernikova; V. Yu. Kalashnikov; T. P. Bardymova; V. K. Protasov; A. Yu. Babenko; et al. (Рациональная фармакотерапия в кардиологии)
The interdisciplinary interim experts’ council on March 3, 2016 in Moscow have considered the EMPA-REG OUTCOME trial results and suggested a number of propositions and recommendations on further empagliflozin’s cardiovascular effects investigation and its clinical application in patients with type 2 diabetes at high cardiovascular risk.